PENERAPAN ASAS IKTIKAD BAIK PADA PERJANJIAN LISAN (NON KONTRAKTUAL) DALAM TRANSAKSI ANTAR PEDAGANG DENGAN PENYUPLAI BARANG DI PASAR KLEWER - Khudzaifah Dimyati; Kelik Wardiono; Budi Winarno (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
Trade is a form of economic activity that has an effect on increasing the economy of a region. The availability of place, time, and goods is not a problem in trade, because the touch of technology is one of the solutions. Technology in buying and selling makes it easier for sellers and buyers to make transactions without meeting and based solely on the principle of good faith. Regarding the problems that occurred in the research process, several respondents admitted that the problems that often arise came from the traders. The use of oral agreements in buying and selling becomes a habit that cannot be abandoned by Klewer Market traders, even though they are aware that their position is weak if there are legal problems in its implementation. The conclusion is that the unwritten agreement entered into by a Trader with a supplier of goods at Klewer Market is still valid and binding on both parties but is weak in terms of proof in case of a civil dispute. On the other hand, we try to review the application of the principles of good faith in oral agreements between traders and suppliers of goods based on local wisdom.